The contribution of management buy-ins to corporate restructuring: concepts, characteristics and performance - Robbie, Ken (1993)
From the mid-1980s many UK venture capitalists, as an extension to their involvement in management buy-outs, made investments in management buy-ins where they backed new managers to purchase equity stakes in an existing company. This Thesis analyses the corporate restructuring and entrepreneurial influences behind buy-ins taking note of turnaround and venture capital influences. It draws on general buy-in characteristics from a database of 750 management buy-ins and the results of a representative questionnaire survey of 59 management buy-ins (mailed in February 1990) and backed by individual case studies. It is hypothesised that management buy-ins are a distinctive corporate restructuring form and have major differences with management buy-outs. Buy-ins are shown to be significantly different from buy-outs in terms of source, activity and realisation; they are more likely to be bought from a private source and to end up in receivership. Financing structures are more conservative but not on a statistically significant basis. Buy-in teams are smaller than in buy-outs, frequently have initial skills gaps, and in a minority of cases are led by second time entrepreneurs. The target company is normally identified through informal networks. Buy-ins are followed by a significantly higher degree of action in financial, product and marketing areas than Buy-outs and other restructuring processes such as turnarounds. Compared to US LBOs more attention is paid to working asset management with little unbundling of fixed assets and higher capital expenditure. Team Leaders are shown to be mainly opportunist in terms of entrepreneurial typology with a minority craftsmen and, unexpectedly, a few mainly motivated by push factors. This is in contrast to buy-outs where a typology is developed showing a preponderance of craftsmen.